The economics of epidemiology - Tassier, Troy (SpringerBriefs in Public Health, 2013)
The book presents a basic introduction to epidemiology from the perspective of economics, using economic modeling to better understand and describe how infectious disease spreads. Three main elements are introduced: epidemiology, social network analysis, and the economics needed to model the behavior of individuals in the presence of infectious disease. The book aims to provide a starting point for discussion between medical professionals, social scientists and public health officials, the three groups interested in the spread of disease.